Comparison between constant and decreasing rest intervals: influence on maximal strength and hypertrophy - de Souza, T. P.; Fleck, S. J.; Simao, R.; Dubas, J. P.; Pereira, B.; de Brito Pacheco, E. M.; da Silva, A. C.; de Oliveira, P. R. (The Journal of Strength and Conditioning Research, 2010)
Most resistance training programs use constant rest period lengths between sets and exercises, but some programs use decreasing rest period lengths as training progresses. The aim of this study was to compare the effect on strength and hypertrophy of 8 weeks of resistance training using constant rest intervals (CIs) and decreasing rest intervals (DIs) between sets and exercises. Twenty young men recreationally trained in strength training were randomly assigned to either a CI or DI training group. During the first 2 weeks of training, 3 sets of 10-12 repetition maximum (RM) with 2-minute rest intervals between sets and exercises were performed by both groups. During the next 6 weeks of training, the CI group trained using 2 minutes between sets and exercises (4 sets of 8-10RM), and the DI group trained with DIs (2 minutes decreasing to 30 seconds) as the 6 weeks of training progressed (4 sets of 8-10RM). Total training volume of the bench press and squat were significantly lower for the DI compared to the CI group (bench press 9.4%, squat 13.9%) and weekly training volume of these same exercises was lower in the DI group from weeks 6 to 8 of training. Strength (1RM) in the bench press and squat, knee extensor and flexor isokinetic measures of peak torque, and muscle cross-sectional area (CSA) using magnetic resonance imaging were assessed pretraining and posttraining. No significant differences (p = 0.05) were shown between the CI and DI training protocols for CSA (arm 13.8 vs. 14.5%, thigh 16.6 vs. 16.3%), 1RM (bench press 28 vs. 37%, squat 34 vs. 34%), and isokinetic peak torque. In conclusion, the results indicate that a training protocol with DI is just as effective as a CI protocol over short training periods (6 weeks) for increasing maximal strength and muscle CSA; thus, either type of program can be used over a short training period to cause strength and hypertrophy.